1997
DOI: 10.1038/sj.ejcn.1600414
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenes from coffee beans decrease serum levels of lipoprotein(a) in humans: results from four randomised controlled trials

Abstract: Objective: Un®ltered coffee raises serum LDL cholesterol in humans, owing to the presence of the diterpenes cafestol and kahweol. Norwegians with a chronic high intake of un®ltered coffee also had elevated serum levels of lipoprotein(a), an LDL-like particle which is insensitive toward dietary interventions. We now experimentally studied the in¯uence of coffee diterpenes on lipoprotein(a) levels. Design: Four randomised controlled trials. Subjects: Healthy, normolipidemic volunteers. Interventions: Coffee, cof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 58 publications
2
13
0
1
Order By: Relevance
“…The magnitude of the serum cholesterol changes in the present study corresponds to the effect of unfiltered coffee in an earlier meta-analysis (Bak, 1990), the review of Urgert and Katan (1997) and results from the Swedish part of the MONICA study (Strandhagen et al 2000, abstract).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The magnitude of the serum cholesterol changes in the present study corresponds to the effect of unfiltered coffee in an earlier meta-analysis (Bak, 1990), the review of Urgert and Katan (1997) and results from the Swedish part of the MONICA study (Strandhagen et al 2000, abstract).…”
Section: Discussionsupporting
confidence: 77%
“…The Lp(a) levels fell, on the other hand during both the coffee periods, which corresponds to Urgert et al (1997) who showed an Lp(a)-reducing effect of diterpenes. The standard deviations of Lp(a) were very wide in the present study, indicating a large interindividual variation.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The beneficial effects include a possible reduction of toxicant activity after consumption of cafestol, whereas the increase in plasma cholesterol concentration can be considered as potentially harmful. Both outcomes are considered as relevant for a normal coffee consumption pattern [1,2,4,7,8,[33][34][35][36]. The present study contributes to a further mechanistic understanding of this balance between beneficial and potentially detrimental effects of cafestol.…”
Section: Discussionmentioning
confidence: 83%
“…Coffee terpenoids, cafestol, kaweol and 16-O-methylcafestol, which occur as fatty acid (FA) esters (FAEs), are responsible for the reversible rise in plasma low-density lipoprotein (LDL) cholesterol (CHOL) observed in some populations (e.g., Scandinavia, Italy) [1][2][3]. High consumption of boiled, unfiltered coffee was linked to risen levels of homocysteine [4,5], which, along with risen CHOL, is a known risk factor for cardiovascular disease (CVD).…”
Section: Introductionmentioning
confidence: 99%